Automated Assembly Technology of Chain and Application of Data Acquisition System - Xu Changming; Zheng Linquan (Jixie chuandong)
Chain transmission is one of the basic machinery,various industry of national economic often require its drive and transport function. A new chain automated assembly line is designed,it including chain assembly,testing device,riveting device,pre- stretch and running- in device,chain length cutting device,it is not only process concentration,also can realize the production for chain with bent plates by sensor to closely co- ordinate each process and the next process. It not only can improve greatly the efficiency of chain automated assembly,also allow digital management system,man- machine interface,all the assembly data will be visualization,reading and mobility,at the same time greatly improve the product quality.